Efficacy of Mamsyadi Ghana capsule and Saraswatarista in the management of Insomnia Disorder - A Randomized Controlled Clinical Trial - M. Manasa; Aswini Padmashali; Basavaraj R. Tubaki; Manisha (Journal of Ayurveda and Integrative Medicine, 2025)
Background: One of the prevalent sleep disorders is insomnia disorder. Current pharmacotherapy have limitations like dependence, tolerance and withdrawal effects. Ayurveda drugs remains to be explored. Objectives: Can Ayurveda intervention (Mamsyadi Ghana Capsule and Saraswatharista) play a role in Insomnia disorder. Material and Methods: 50 patients meeting the diagnostic criteria of Insomnia Disorder (DSM 5), age group 20–70 years, either sex participated in the study. They were randomly divided and Ayurveda group received Mamsyadi Ghana Capsule 500 mg, Saraswatharista 10 ml, with equal quantity of water after food, both thrice a day for 30 days. Zolpidem group received tablet Zolpidem 10 mg once a day at bed time. Evaluations were done through Insomnia severity Index (ISI), Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness scale (ESS), Sleep diary parameters, Depression Anxiety and Stress Scale (DASS), Quality of Life – SF 36 Questionnaire and UKU side effect rating scale. Clinical assessments were at baseline, 15th and 30th day. Results: The study showed that Ayurveda intervention produced significant improvement and was comparable to Zolpidem. Both interventions were comparable in ISI, PSQI, ESS, DASS scale, sleep diary parameters and most of the components of SF-36. Role of limitations due to emotional problems component showed better improvement in Ayurveda group (p = 0.01). Within group analysis showed improvement in both the groups. Five patients had adverse effects with Zolpidem and nil with ayurveda group. Conclusions: The study showed that effect of Ayurveda interventions (Mamsyadi Ghana Capsule and Saraswatharista) is comparable to zolpidem in Insomnia Disorder. Ayurveda intervention had better improvement on quality of life and had good safety profile. Ctri registration number: CTRI/2021/12/038809.